Globalization and cultural diversity on campus: A study of intercultural interactions - Belianti, Inaya Dwi; Surya, Rachmad Iqbal; Sya'bana, Sya'rifatus (Direktorat Riset dan Pengabdian kepada Masyarakat UNY, 2025)
Globalization has had a significant impact on various aspects of life, including in the context of higher education. This study aims to explore intercultural interactions in regional student communities at the Faculty of Social and Political Sciences (FISIP) of Sunan Ampel State Islamic University (UIN) Surabaya, as a response to the phenomenon of globalization and cultural diversity. The method chosen in this research was to gain an in-depth understanding of intercultural interactions in the academic area student community at UIN Sunan Ampel Surabaya. Case study research on research subjects related to globalization which brings changes in student interactions. Intercultural interaction among students in the era of globalization is a specific or typical phase of the overall personality. The results of the research show that globalization has made positive and negative contributions to intercultural interaction at FISIP UIN Sunan Ampel Surabaya. On the one hand, the exchange of ideas and experiences between students and lecturers from various cultures has enriched the academic experience. On the other hand, there are challenges in managing cultural differences that may cause conflicts or misunderstandings.